Sustainable development goals: Transportation, health and public policy - Vahid Mohamad Taghvaee; Abbas Assari Arani; Mehrab Nodehi; Jalil Khodaparast Shirazi; Lotfali Agheli; Haji Mohammad Neshat Ghojogh; Nafiseh Salehnia; Amir Mirzaee; Saeed Taheri; Raziyeh Mohammadi Saber; Hady Faramarzi; Reza Alvandi; et al. (Review of Economics and Political Science (REPS), 2023)
Purpose This study aims to assess and decompose the sustainable development using the 17 sustainable development goals (SDGs) in Iran in 2018, for proposing agenda-setting of public policy. Design/methodology/approach It ranks the SDGs not only in Iran but also in the region and the world to reveal the synergetic effects. Findings Based on the results, subaltern-populace generally suffers from the hegemonic domination of ruling elite-bourgeois, lack of strong institutions, heterogeneous policy networks and lack of advocacy role of non-governmental organizations, due to no transparency, issues in law or no rule of law, no stringent regulation, rent, suppression and Mafia, all leading to corruption and injustice. Practical implications To stop the loop of corruption-injustice, Iran should homogenize the structure of the policy network. Furthermore, the failed SDGs of the three-geographic analysis are the same in a character; all of them propose SDG 3, good health and well-being as a serious failed goal. Social implications In this regard, strong evidence is the pandemic Coronavirus, COVID 19 since 2019, due to its highly-disastrous consequences in early 2020 where the public policymakers could not adopt policies promptly in the glob, particularly in Iran. Originality/value In Iran, in addition to this, the malfunction of health is rooted in "subjective well-being" and "traffic deaths," respectively. Concerning the transportations system in Iran, it is underscored that it is damaging the sustainable development from all the three pillars of sustainable development including, economic, social and environmental.
Keywords: H83; I15; Q56; R41; 330; Health; Policy network; Public policy; Sustainable development goals; Transportation